Ethnobotanical, phytochemical, pharmacological, and toxicological aspects of Persicaria hydropiper (L.) Delarbre - Moyeenul Huq, A. K. M.; Jamal, Jamia Azdina; Stanslas, Johnson (Hindawi Publishing Corporation, 2014)
Persicaria hydropiper (L.) Delarbre, belonging to Polygonaceae family, is a common weed found in most of the temperate countries including Bangladesh, China, Malaysia, and Japan. The plant is also referred to as “marsh pepper” or “smart weed.” It appears to be a useful herb with evidence-based medicinal properties. The present work addresses the botanical description, traditional uses, phytochemistry, pharmacology, and toxicology of P. hydropiper. All plant parts have been commonly used in the traditional systems of medicines. Flavonoids are the major group of phytochemical components followed by drimane-type sesquiterpenes and sesquiterpenoids, as well as phenylpropanoids. Different extracts and plant parts showed remarkable pharmacological activities including antioxidant, antibacterial, antifungal, antihelminth, antifeedant, cytotoxicity, anti-inflammatory, antinociceptive, oestrogenicity, antifertility, antiadipogenicity, and neuroprotection. Mutagenicity and acute and subchronic toxicities of the plant were also reported. P. hydropiper has tremendous medicinal properties that could further be investigated for the development of evidence-based herbal products.